Improvement of fatigue resistance on La modified BiFeO(3) thin films - Simões, Alexandre Zirpoli [UNESP]; Cavalcante, L. S.; Riccardi, C. S. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2009)
The effect of lanthanum (La) addition in BiFeO(3) (BFO) thin films deposited on Pt(111)/Ti/SiO(2)/Si(100) substrates prepared by soft chemical method was explained. Increasing La concentration promotes changes on structure, microstructure and dielectric/ferroelectric response of films. X-ray diffraction reveals that the films are free of preferred orientations and structural distortion. La addition promotes an increase in dielectric permittivity. The polarization switching and the fatigue behavior of the BFO films were significantly enhanced by the La concentration. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Fatigue resistance; BiFeO(3); Ferroelectric; Multiferroic